HUBUNGAN LAJU FILTRASI GLOMERULUS DENGAN KADAR HEMOGLOBIN PADA PASIEN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT BUDI KEMULIAAN KOTA BATAM - Sukma Sahreni; Sudarsono; Yoel Pelawi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background : Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia, which is a condition in which blood sugar levels increase which can cause serious damage to the body's systems, especially blood vessels and respiration. Methods : This study used a quantitative analytic research design with a cross sectional study approach. The research was conducted at Budi Kemuliaan Hospital Batam in February 2022. The sampling technique was consecutive sampling with a sample of 214 people. Data collection using medical records. Data analysis using the Chi-Square test statistic. Results : From the results of the study, it was found that there was a relationship between glomerular filtration rate and hemoglobin levels in diabetes mellitus patients and a significant p-value was obtained of 0.003 Conclusion : Based on the results of data processing it can be concluded that there is a significant relationship between glomerular filtration rate and hemoglobin levels in type 2 diabetes mellitus patients at Budi Kemuliaan Hospital Batam in 2021